BUSINESS JUDGMENT RULES AND IMPOSITION OF STATE LOSSES ON STATE-OWNED ENTERPRISES WHICH LOSSES DUE TO OWNERSHIP OF AN ASSET SOURCED FROM ACCUMULATION OF PENSION CONTRIBUTIONS - Nia Sari Damanik, Patricia (Awang Long Law Review, 2024)
This article aims to examine and analyze the limitations of implementations of Business Judgment Rule and the imposition of state financial losses on State-Owned Emterprise due to losses in asset which is financed by accumulated pension contributions. The problem is focused on the application of the Business Judgment Rule for accumulated pension contributions losses due to ownership of the JMP stand/kiosk in Surabaya and the imposition of state financial losses on that losses. This research is doctrinal legal research which uses interpretive methods to analyze cases of Director’s decision at BUMN X, the results of which are then developed into descriptive analysis. Based on the theory of Business Judgment Rules, State Finances, and State Losses, it is concluded that the loss in Accumulated Pension Contributions from the ownership of the JMP stand/kiosk is not a state loss and BUMN X Directors cannot be blamed for this loss. This research suggests the Director to do the cut loss immediately by selling the 18 stands/kiosks and continuing to encourage the Minister of Finance to issue implementing regulations of Undang-Undang Nomor 4 Tahun 2004 tentang Pengembangan dan Penguatan Sektor Keuangan as a basis for the cut loss.